Characterization of complete mitochondrial genome of Chionobathyscus dewitti (Perciformes, Channichthyidae). - Sapto Andriyono, ,- (Taylor & Francis, 2019)
The complete mitochondrial genome sequence of the Icefish, Chionobathyscus dewitti was determined by the Next Generation Sequencing (NGS) analysis. The complete mitogenome was 17,452 bp in length, which encoded the canonical 13 protein-coding genes, 22 tRNAs, two rRNAs, and two non-coding regions. As shown in the other notothenids, translocation of ND6 and an additional non–coding region were identified, which is different from the typical vertebrate mitochondrial genomes. The C. dewitti was clustered distinctly from the those in the Chinodraco and Chaenocephalus, which supported the idea that this species should be classified in the different genus, Chionobathyscus in the family Channichthyidae